2018
DOI: 10.1159/000495352
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Steroid Regimen for Adult Steroid-Sensitive Minimal Change Disease

Abstract: Background: In pediatric patients with steroid-sensitive nephrotic syndrome, recent trials have revealed that a 2-month, short-term steroid regimen is not inferior to an extended steroid course. However, the optimal duration of initial steroid therapy for adult steroid-sensitive minimal change disease (MCD) remains unclear. Objectives: The aim of present study was to evaluate the effectiveness of a 2-month, short-term steroid regimen in the treatment of adult steroid-sensitive MCD patients. Method: This was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
6
0
3
Order By: Relevance
“…Several guidelines suggested longer corticosteroid therapy; the Kidney Disease Improving Global Outcomes (KDIGO) clinical guideline for glomerulonephritis suggested a daily dose of 1.0 mg/kg of prednisolone or an alternate-day single dose of 2 mg/kg tapered slowly over a total period of up to 6 months [12] and the Japanese evidence-based clinical practice guideline for nephrotic syndrome suggest 0.6-0.8 mg/kg of prednisolone tapered within 2 years [13]. Compared with these conventional long corticosteroid therapies, an intriguing Japanese observational study of adult patients with MCD suggested clinical advantages of a 2-month corticosteroid therapy, the lower incidence of adverse events, including diabetes and infection [31]. Because nephrologists might possibly maintain adult patients with MCD on corticosteroids for very long [32], an optimal immunosuppressive therapy should be explored in well-designed clinical studies to prevent critical events associated with immunosuppressive therapy, including infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several guidelines suggested longer corticosteroid therapy; the Kidney Disease Improving Global Outcomes (KDIGO) clinical guideline for glomerulonephritis suggested a daily dose of 1.0 mg/kg of prednisolone or an alternate-day single dose of 2 mg/kg tapered slowly over a total period of up to 6 months [12] and the Japanese evidence-based clinical practice guideline for nephrotic syndrome suggest 0.6-0.8 mg/kg of prednisolone tapered within 2 years [13]. Compared with these conventional long corticosteroid therapies, an intriguing Japanese observational study of adult patients with MCD suggested clinical advantages of a 2-month corticosteroid therapy, the lower incidence of adverse events, including diabetes and infection [31]. Because nephrologists might possibly maintain adult patients with MCD on corticosteroids for very long [32], an optimal immunosuppressive therapy should be explored in well-designed clinical studies to prevent critical events associated with immunosuppressive therapy, including infection.…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences in the time from the initiation of PSL to relapse and in the relapse rate between the two groups [ 11 ]. Similar protocols have also been compared in adults where a 2-month short-term steroid regimen resulted in a higher relapse rate and shorter time to relapse than the conventional steroid regimen with a similar initial therapy dosage (0.8–1.0 mg/kg/day) [ 14 ]. In adults, short-term dosing is not as effective as it is in children with regard to the relapse rates, and it may be more effective to reduce the initial PSL dose, prolong treatment, and then taper the dosage down.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 213 accumulative cases of infectious complications of adult MCNS were reported among 1787 patients from four randomized controlled trials (RCTs), 7–10 12 observational studies 5,14–24 and patients of our hospital (Table 5). The published studies showed various incidences of infectious complications while none investigated the risk factor.…”
Section: Resultsmentioning
confidence: 99%